Current Aspects in the Biology, Pathogeny, and Treatment of Candida krusei, a Neglected Fungal Pathogen - Gómez-Gaviria M; Mora-Montes HM (Infection and Drug Resistance, 2020)
Manuela Gómez-Gaviria, Héctor M Mora-Montes Departamento de Biología, División de Ciencias Naturales y Exactas, Campus Guanajuato, Universidad de Guanajuato, Guanajuato, Gto, MéxicoCorrespondence: Héctor M Mora-MontesDepartamento de Biología, División de Ciencias Naturales y Exactas, Campus Guanajuato, Universidad de Guanajuato, Noria Alta s/n, Col. Noria Alta, C.P. 36050, Guanajuato, Gto, MéxicoTel +52 473-7320006 Ext. 8193Fax +52 473-7320006 Ext. 8153Email hmora@ugto.mxAbstract: Fungal infections represent a constant and growing menace to human health, because of the emergence of new species as causative agents of diseases and the increment of antifungal drug resistance. Candidiasis is one of the most common fungal infections in humans and is associated with a high mortality rate when the fungi infect deep-seated organs. Candida krusei belongs to the group of candidiasis etiological agents, and although it is not isolated as frequently as other Candida species, the infections caused by this organism are of special relevance in the clinical setting because of its intrinsic resistance to fluconazole. Here, we offer a thorough revision of the current literature dealing with this organism and the caused disease, focusing on its biological aspects, the host-fungus interaction, the diagnosis, and the infection treatment. Of particular relevance, we provide the most recent genomic information, including the gene prediction of some putative virulence factors, like proteases, adhesins, regulators of biofilm formation and dimorphism. Moreover, C. krusei veterinary aspects and the exploration of natural products with anti-C. krusei activity are also included.Keywords: virulence, candidiasis, host-fungus interplay, antifungal drug, immune sensing